The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.rser.2020.110243
|View full text |Cite
|
Sign up to set email alerts
|

Multicriteria-based methodology for the design of rural electrification systems. A case study in Nigeria

Abstract: Electrification with micro-grids is receiving increasing attention to electrify rural areas in developing countries. However, determining the best local supply solution is a complex problem that requires considering different generation technologies (i.e. solar PV, wind or diesel) and different system configurations (off-grid or on-grid). Most existing decision aid tools to assess this design only consider economical and technical issues in a single optimization process. However, social and environmental consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The reason to select this location is to impart benefits of electrification to the community, which were shown in another similar location in Tanzania (Ngowi et al, 2019), India (Jamasb et al, 2015), and Zimbabwe (Davidson and Mwakasonda, 2004). Further, grid connection feasibility depends on community size and the distance from the closest grid point (Juanpera et al, 2020;Karhammar, 2006), and for the case study of this paper, the community size is sparse populated, about 20 km from the grid, and rural location. Da Silva et al (2001) showed a cost saving of 29% for a RE in Uganda, if SWER is used to connect about 200,000 inhabitants of rural remote areas.…”
Section: Case Study In Tanzaniamentioning
confidence: 89%
“…The reason to select this location is to impart benefits of electrification to the community, which were shown in another similar location in Tanzania (Ngowi et al, 2019), India (Jamasb et al, 2015), and Zimbabwe (Davidson and Mwakasonda, 2004). Further, grid connection feasibility depends on community size and the distance from the closest grid point (Juanpera et al, 2020;Karhammar, 2006), and for the case study of this paper, the community size is sparse populated, about 20 km from the grid, and rural location. Da Silva et al (2001) showed a cost saving of 29% for a RE in Uganda, if SWER is used to connect about 200,000 inhabitants of rural remote areas.…”
Section: Case Study In Tanzaniamentioning
confidence: 89%
“…Conversely, Li et al [ 21 ] reported a BGED of 9.71 km for a remote village in West China which can be potentially powered by biomass, wind and solar energy resources. As a rule of thumb, Juanpera et al [ 22 ] noted that extending the grid to a remote community in Nigeria is only feasible when the community is large and at a distance not longer than 25 km to the national grid.…”
Section: Studies On Mini-gridmentioning
confidence: 99%
“…The same goes for taking into account good practices that have been identified in different case studies to make better assumptions when estimating the chances of success of new microgrid projects [69,201]. Finally, some studies go a little deeper by providing complete models for microgrid deployment [202], systemic methods for microgrid design [51,203], or techno-economic optimization frameworks [204,205].…”
Section: Financial Issuesmentioning
confidence: 99%